Effect of breastfeeding promotion interventions on breastfeeding rates, with special focus on developing countries - Bhutta Zulfiqar A; Yakoob Mohammad Yawar; Imdad Aamer (BMC, 2011)
Abstract Background Given the recognized benefits of breastfeeding for the health of the mother and infants, the World Health Organization (WHO) recommends exclusive breastfeeding (EBF) for the first six months of life. However, the prevalence of EBF is low globally in many of the developing and developed countries around the world. There is much interest in the effectiveness of breastfeeding promotion interventions on breastfeeding rates in early infancy. Methods A systematic literature was conducted to identify all studies that evaluated the impact of breastfeeding promotional strategies on any breastfeeding and EBF rates at 4-6 weeks and at 6 months. Data were abstracted into a standard excel sheet by two authors. Meta-analyses were performed with different sub-group analyses. The overall evidence were graded according to the Child Health Epidemiology Reference Group (CHERG) rules using the adapted Grading of Recommendations, Assessment, Development and Evaluation (GRADE) criteria and recommendations made from developing country studies for inclusion into the Live Saved Tool (LiST) model. Results After reviewing 968 abstracts, 268 studies were selected for potential inclusion, of which 53 randomized and quasi-randomized controlled trials were selected for full abstraction. Thirty two studies gave the outcome of EBF at 4-6 weeks postpartum. There was a statistically significant 43% increase in this outcome, with 89% and 20% significant increases in developing and developed countries respectively. Fifteen studies reported EBF outcomes at 6 months. There was an overall 137% increase, with a significant 6 times increase in EBF in developing countries, compared to 1.3 folds increase in developed country studies. Further sub-group analyses proved that prenatal counseling had a significant impact on breastfeeding outcomes at 4-6 weeks, while both prenatal and postnatal counseling were important for EBF at 6 months. Conclusion Breastfeeding promotion interventions increased exclusive and any breastfeeding rates at 4-6 weeks and at 6 months. A relatively greater impact of these interventions was seen in developing countries with 1.89 and 6 folds increase in EBF rates at 4-6 weeks and at 6 months respectively.